Hematological parameter changes and associated factors in neonates with hyperbilirubinemia treated with phototherapy - Adamu Kassie; Dereje Mengesha Berta; Aregawi Yalew; Chomaw Sitotaw; Mickael Workineh; Berhanu Woldu (BMC Pediatrics)
Abstract Background Phototherapy is a common treatment for neonatal hyperbilirubinemia, however it generates reactive oxygen species and induces apoptosis, potentially influencing blood cells. Assessing changes in hematological parameters is essential to minimize complications and enhance outcomes. Objective This study assessed hematological parameters changes and associated factors in neonates with hyperbilirubinemia undergoing phototherapy. Method A cross-sectional study was conducted at the University of Gondar Comprehensive Specialized Hospital from May 29 to November 8, 2023. About 246 neonates were selected by convenient sampling. Blood samples were collected before and after phototherapy. Data were entered into Epi-data (4.6.0) and analyzed using SPSS (25.0). The normality of the data was checked by Kolmogorov-Smirnov tests. A paired t-test and Wilcoxon Sign Rank test were used to compare mean differences for normally distributed and skewed data, respectively. Pearson correlation and multiple linear regressions were used to measure the association. A significance level of p < 0.05 was used for statistical significance. Result Among neonates, 141 (57.3%) were males, and the median age was 2 days. Phototherapy treatment led to significant increases in WBC and lymphocyte count, 11.02 ± 2.21 to 11.35 ± 2.60, and 3.93 ± 1.19 to 4.16 ± 1.34, respectively. However, hemoglobin and platelet count significantly decreased from 15.05 ± 3.67 to 14.55 ± 2.62, and 243.23 ± 74.78 to 239.32 ± 73.29, respectively. Other blood cell parameters were unaffected. WBC and lymphocytes showed a positive association with preterm neonates and intensive phototherapy, while WBC count showed a negative association with total bilirubin. Hemoglobin counts are positively associated with total bilirubin but negatively associated with neonate age and treatment duration. Platelet count showed negative associations with low-birth-weight neonates, intensive phototherapy, and treatment duration. After treatment, normocytic normochromic cells increased, microcytic hypochromic decreased, and abnormal RBC shapes were reduced. Conclusion Phototherapy significantly affected key hematological parameters, notably WBC, lymphocytes, hemoglobin, and platelet count. Treating neonates with intensive phototherapy affects WBC and platelet counts while undergoing phototherapy for a longer duration affects hemoglobin and platelet counts. Therefore, routine monitoring of these parameters is crucial for neonates undergoing intensive or prolonged phototherapy.